2022
DOI: 10.3389/fpsyt.2022.1013698
|View full text |Cite
|
Sign up to set email alerts
|

Association between lipid metabolism and cognitive function in patients with schizophrenia

Abstract: BackgroundThe association between blood lipids and cognitive function in schizophrenia is still controversial. Thus, the present study aimed to verify the association between various lipid parameters and cognitive impairment in schizophrenic patients and potential lipid pathways.MethodsA total of 447 adult inpatients with schizophrenia were divided into cognitive normal and cognitive impairment groups based on the Mini-Mental State Examination with a cut-off of 26. The blood lipid parameters were defined as ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Regarding diet, although a recent study ( Barnes et al, 2023 ) showed no significant difference between participants with a family history of dementia and no cognitive impairment on the MIND diet and a mildly calorie-restricted control diet, there are studies ( Millman et al, 2021 ; Roschel et al, 2021 ) that suggest that certain foods and nutrients, such as primary olive oil and creatine, have beneficial effects on cognitive function. Regarding lipids and blood pressure, a Chinese study ( Lee et al, 2021 ) that included 2,215 participants showed that DSST scores increased with an increase in HDL (β coefficient: 0.036; p = 0.018), while a study by Liu et al (2022) found a positive correlation between lipids and cognitive function in people with schizophrenia. Mahinrad et al (2020) showed a positive correlation between blood lipids and cognitive function in people with schizophrenia, ranging from young to exposure to higher blood pressure levels during middle age was associated with poorer gait and cognitive performance during middle age.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding diet, although a recent study ( Barnes et al, 2023 ) showed no significant difference between participants with a family history of dementia and no cognitive impairment on the MIND diet and a mildly calorie-restricted control diet, there are studies ( Millman et al, 2021 ; Roschel et al, 2021 ) that suggest that certain foods and nutrients, such as primary olive oil and creatine, have beneficial effects on cognitive function. Regarding lipids and blood pressure, a Chinese study ( Lee et al, 2021 ) that included 2,215 participants showed that DSST scores increased with an increase in HDL (β coefficient: 0.036; p = 0.018), while a study by Liu et al (2022) found a positive correlation between lipids and cognitive function in people with schizophrenia. Mahinrad et al (2020) showed a positive correlation between blood lipids and cognitive function in people with schizophrenia, ranging from young to exposure to higher blood pressure levels during middle age was associated with poorer gait and cognitive performance during middle age.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an association between cognitive impairment and TG, but no significant relation was found between HDL and LDL. Liu et al [ 56 ] found the association between lipid parameters and cognitive impairment was heterogeneous in age and gender subgroups. On the contrary, the nonsignificant result was reported by a recent systematic review that cognitive function in all domains did not differ in SSD with or without dyslipidemia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid parameters including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) have been found to associate with cognitive impairment in multiple diseases, such as patients with post-stroke and Parkinson's Disease [ 6 , 7 ]. In addition, apolipoprotein B has been shown to be associated with cognitive function in patients with schizophrenia [ 8 ]. Interesting, apolipoprotein A1 has been involved in the earliest stages of Alzheimer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%